Fermentation Microbiology and Biotechnology - El-Mansi, Mansi; Ed (Taylor & Francis, 1999)
Fermentation biotechnology, as a result of genetic engineering and advances in computer science, is progressing rapidly. This book addresses the multidisciplinary nature of fermentation and should be of value to industrialists and microbiologists.